2005
DOI: 10.1089/neu.2005.22.106
|View full text |Cite
|
Sign up to set email alerts
|

The Neurosteroids Progesterone and Allopregnanolone Reduce Cell Death, Gliosis, and Functional Deficits after Traumatic Brain Injury in Rats

Abstract: This report compares the effects of progesterone and its metabolite, allopregnanolone, on the early injury cascade (apoptosis) and long-term functional deficits after TBI. Progesterone (16 mg/kg) or allopregnanolone (4, 8, or 16 mg/kg) were injected at 1 h, 6 h, and then for 5 consecutive days after bilateral contusions of the frontal cortex in adult male rats. Within one day after injury, progesterone and allopregnanolone reduced both the expression of pro-apoptotic proteins caspase-3 and Bax, and apoptotic D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
255
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 353 publications
(270 citation statements)
references
References 37 publications
12
255
1
2
Order By: Relevance
“…In vitro studies in organotypic brain slice cultures have previously shown that pretreatment with allopregnanolone reduces astrogliosis following a hypoxic insult (Kruse et al 2009). Studies of traumatic brain injury in adult rats have also shown that both progesterone and allopregnanolone administration reduces the size of GFAP-positive astrocytes (Djebaili et al 2005). Despite the increase in GFAP expression when allopregnanolone synthesis was inhibited, qualitative analysis identified no overt areas of glial scarring or obvious signs of damage related to GFAP staining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies in organotypic brain slice cultures have previously shown that pretreatment with allopregnanolone reduces astrogliosis following a hypoxic insult (Kruse et al 2009). Studies of traumatic brain injury in adult rats have also shown that both progesterone and allopregnanolone administration reduces the size of GFAP-positive astrocytes (Djebaili et al 2005). Despite the increase in GFAP expression when allopregnanolone synthesis was inhibited, qualitative analysis identified no overt areas of glial scarring or obvious signs of damage related to GFAP staining.…”
Section: Discussionmentioning
confidence: 99%
“…The suppression of allopregnanolone synthesis increases markers of cell proliferation, an effect that is ameliorated when the synthetic neurosteroid, alfaxalone, is used to replace the loss of the endogenous neurosteroid (Yawno et al 2009). In adult rat models of traumatic brain injury, allopregnanolone administration has also reduced the size of GFAP-positive astrocytes at the site of the experimental lesions (Djebaili et al 2005), and there is increasing evidence for the effectiveness of allopregnanolone in reducing lesion size and enhancing functional recovery in animal models of traumatic brain injury (Djebaili et al 2004, Schumacher et al 2007. In addition to the previously reported neuroprotective actions of allopregnanolone, this study provides evidence of delayed neurodevelopment in the presence of a low neurosteroid environment and suggests an important role of allopregnanolone in the regulation of developmental processes in the late gestation foetal brain.…”
Section: Discussionmentioning
confidence: 99%
“…In rats with bilateral medial frontal cortex (MFC) contusions, post-injury injections of PROG reduced cerebral edema, blood-brain barrier disruption, and the expression of inflammatory cytokines [7,31,32]. We have also shown that PROG's metabolite, allopregnanolone (ALLO; 5α-pregnan-3β-ol-20-one), a GABA-A agonist, can reduce the mediators of inflammation after TBI at a dose that is 50% lower than PROG [14].…”
Section: Introductionmentioning
confidence: 96%
“…These include neuroprotection against ischemia and stroke (Cutler, et al, 2005,Djebaili, et al, 2005,Hoffman, et al, 2003,Lapchak, 2004,Meffre, et al, 2007,Shear, et al, 2002,VanLandingham, et al, 2006, recovery of motor function after spinal cord injury (di Michele, et al, 2000,Fiore, et al, 2004,Labombarda, et al, 2006,Patte-Mensah, et al, 2004,Pomata, et al, 2000, regulation of myelination (Chavez-Delgado, et al, 2005,Gago, et al, 2001,Ghoumari, et al, 2005,Ghoumari, et al, 2003,Le Goascogne, et al, 2000,Schumacher, et al, 2000,Schumacher, et al, 2004, proliferation of neuronal stem cells (Suzuki, et al, 2004,Wang, et al, 2005 , neurogenesis in the hippocampus (Keller, et al, 2004,Suzuki, et al, 2004,Wang, et al, 2005, and induction of analgesia (Pathirathna, et al, 2005,Todorovic, et al, 2004. Many of these actions of neurosteroids are discussed in detail in other papers in this issue.…”
Section: Introductionmentioning
confidence: 99%